Sustentabilidade e forma urbana: estudo de caso aplicado à cidade de Uberaba-MG - CUSTÓDIO, Veruska Bichuette (2018)
The growth of cities in number and size coupled with losses in environmental and living quality call into question the organization and appropriation of land and resources in cities. From the viewpoint of sustainable development established in the 1990s, urbanism seeks solutions to make urban spaces economically fairer, environmentally less aggressive and socially balanced. The different solutions proposed have similarities as to the materiality, distribution, connection and organization of urban elements such as blocks, streets, buildings and open spaces in the territory demonstrating a common discourse on sustainable urban form. The compact, dense, diverse and integrated city, green and suitable to the place where it is inserted becomes the very materialization of urban sustainability. Thus, the adequacy or inadequacy of these characteristics in cities is an indicator of how sustainable or unsustainable the city is. To quantify the attributes of sustainable urban form, spatial metrics are used to translate urban reality into numerical form to support urban planning and design actions. The use of the study of the urban form as indicative of sustainability although recent has been emphasized in the literature on the subject. Considering this, the present research seeks to approach the notions of sustainability and urban form, spatial metrics and characteristics of the sustainable urban form in order to verify the scope and limitations of this approach for the urban planning and design actions of more sustainable cities in the context of the Brazilian medium-sized cities for this purpose the city of Uberaba-MG is used as a case study.